Periparturient rumen undegradable protein and colostrum quality in Dohne Merino and Meatmaster ewes - Seegmuller, Andre Joseph (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024